Design and implementation of 4-quadrant chopper for speed control of EVs and regenerative braking analysis - Abdelfatah, Magdy Saoudi; Solanki, Parmal Singh; Sreedharan, Sasidharan (Institute of Advanced Engineering and Science, 2025)
This paper presents a novel 4-quadrant chopper design for controlling the speed of electric vehicles, featuring a regenerative braking mechanism to improve energy efficiency. Regenerative braking recovers energy during deceleration by converting kinetic energy into electrical energy stored in the battery. This process activates automatically when the accelerator pedal is released, slowing the vehicle while reducing reliance on mechanical brakes, which remain available for emergency situations. The system’s voltage control is achieved using a pulse-width modulation (PWM) technique that adjusts the duty cycle of switching devices. A microcontroller serves as the system’s core, generating PWM signals and coordinating its operation. The performance of the chopper was evaluated through simulations and experiments, demonstrating that optimal energy recovery occurs at duty cycles of 55-65%. The results revealed that up to 400 joules of energy can be regenerated per braking cycle, particularly in stop-start driving conditions. This innovative design contributes to a 5-10% extension in battery life per charge cycle, enhancing the overall efficiency and sustainability of electric vehicles. The proposed system demonstrates significant potential for energy recovery and reduced wear on mechanical braking systems, paving the way for more efficient electric vehicle technologies.